Complexity Analysis of EEG Data in Persons With Depression Subjected to Transcranial Magnetic Stimulation - Lebiecka, Karolina; Zuchowicz, Urszula; Wozniak-Kwasniewska, Agata; Szekely, David; Olejarczyk, Elzbieta; David, Olivier (Frontiers in Physiology, 2018)
Aim: The aim of this work was to study the neurophysiological effect of repetitive transcranial magnetic stimulation (rTMS) applied to the left dorsolateral prefrontal cortex (DLPFC) in 8 patients with major depression disorder (MDD) and 10 patients with bipolar disorder (BP), considering separately responders and nonresponders to rTMS therapy in each of both groups. Methods: The Higuchi’s Fractal Dimension (FD) was analyzed from 64-channels EEG signals in five physiological frequency bands and every channel separately. Changes of FD were analyzed before and after 1st, 10th and 20th session of rTMS. Results: Some differences in response to the rTMS therapy was found across individual groups. In MDD responders, FD decreased in all bands after longer stimulation (20th session). Whereas, in BP nonresponders, FD decreased after 1st session in all bands as well as after 10th session in lower frequencies (delta and theta). In MDD nonresponders and BP responders FD increased at the beginning of the therapy (1st and 10th session, respectively), but the final FD value did not changed in comparison to the initial FD value, except the FD decrease for theta band in BP responders. Comparison between groups showed a higher FD in MDD responders than in MDD nonresponders in every band before as well as after stimulation. In contrast to MDD patients, FD was lower in BP responders than in BP nonresponders in higher frequency bands (alpha, beta and gamma) in both conditions as well as in lower frequency bands (delta and theta) after stimulation. Comparing both groups of responders, FD was lower in MDD than in BP in every band, except alpha. In case of nonresponders, FD was higher in BP than in MDD in all bands in both conditions. Conclusions: The results showed that FD may be useful marker for evaluation of the rTMS effectiveness and the therapy progress as well as for group differentiation between MDD and BP or between responders and nonresponders. The changes of FD under the influence of rTMS allow to unambiguously conclude whether the effect of stimulation is positive or negative as well as allow to evaluate an optimal time of rTMS.